Plasticity in plant defense and the role of phytochemical dissimilarity in limiting specialist herbivory - Rabelo, Raiane Serejo; Dyer, Lee A.; Yamaguchi, Lydia Fumiko; Diniz, Ivone; Simbaña, Wilmer; Kussano, André Jun Miura; Kato, Massuo Jorge; Massad, Tara Joy (Frontiers in Ecology and Evolution, 2023)
Phytochemical diversity is an effective plant defensive attribute, but much more research has focused on genetic and environmental controls of specific defensive compounds than phytochemical diversity per se. Documenting plasticity in phytochemical richness and plant chemical composition as opposed to individual compounds is important for understanding the overall allocation to defense. This study outlines a multi-site transplant experiment in Cerrado gallery forests in central Brazil, utilizing Piper arboreum (Piperaceae), a prevalent and widespread neotropical shrub. Clones from four distinct populations were planted either at their origin site or in a different forest. Secondary metabolite composition varied between populations initially and then changed after transplanting. Interestingly, clones with chemical profiles that were distinct from the populations where they were introduced experienced reduced specialist chrysomelid herbivory compared to clones that were more chemically similar to the existing P. arboreum populations where they were planted. Specialist Lepidoptera herbivory also declined in clones transplanted to a new forest, but this change could not be ascribed to chemical profiles. In contrast, generalist herbivory was unaffected by chemical dissimilarity and transplanting. This research adds to the expanding body of evidence suggesting that phytochemical diversity is a dynamic trait exerting unique effects on different herbivore guilds.